An investigation on rotatory bending fretting fatigue damage of railway axles. (14th August 2013) - Song, C.; Shen, M. X.; Lin, X. F.; Liu, D. W.; Zhu, M. H.
ABSTRACT Fretting damage failure analysis of a Chinese carbon railway axle RD2 was carried out. The wheel hub was in situ cut to expose the damaged surface of the wheel seat to avoid additional damage. A small‐scale axle test rig was developed, and simulation tests were performed at different rotator speeds of 1800 and 2100 rpm. The wear mechanism of fretting damage areas was a combination of abrasive wear, oxidative wear and delamination. The fracture surfaces exhibited characterization of multisource and step‐profile. The fretting fatigue crack initiated at the subsurface and propagated along an inclined angle at the first stage. The fretting damage at the higher speed was more severe compared with the lower speed, which lead to a relatively shorter fatigue life. The damage morphologies of the axle in the simulation tests were in good agreement with that observed in the failure analysis on real axle.